2021
DOI: 10.1002/we.2597
|View full text |Cite
|
Sign up to set email alerts
|

Methodology for the energetic characterisation of rain erosion on wind turbine blades using meteorological data: A case study for The Netherlands

Abstract: Rain erosion on the leading edge of wind turbine blades is an intricate engineering challenge for the wind industry. Based on an energetic approach, this work proposes a methodology to characterise the erosion capacity of the raindrop impacts onto the leading edge blades. This methodology can be used with meteorological data from public institutions or from direct measurements at the wind turbine locations. The erosion characterisation is analysed using accumulative and per impact erosive variables, that is, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…The result is consistent with analysis from a shorter period, using another wind turbine as an example and extrapolation of winds to hub height including terrain and roughness effects [17]. A study in the Netherlands also found shorter lifetime near the coastline than inland [9]. Grosser Arber has a very short lifetime and high AEP.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The result is consistent with analysis from a shorter period, using another wind turbine as an example and extrapolation of winds to hub height including terrain and roughness effects [17]. A study in the Netherlands also found shorter lifetime near the coastline than inland [9]. Grosser Arber has a very short lifetime and high AEP.…”
Section: Discussionsupporting
confidence: 84%
“…Hail is observed less frequently than rain in Northern Europe [3] but has a high erosion potential [4][5][6]. Rain events occurring during times with high tip speeds cause the most LEE [1,[7][8][9]. Future offshore turbines may operate with even higher tip speeds than current turbines because of their longer blades.…”
Section: Introductionmentioning
confidence: 99%
“…These analyses illustrate that the US SGP exhibits a hydroclimate that differs substantially relative to sites in Europe with respect to parameters of importance to wind turbine blade LEE. Indeed, hail may dominate LEE in the US SGP [92], in contrast to northern Europe where the hydroclimate is dominated by liquid precipitation, hail is very infrequent (Table 2) and thus kinetic energy transfer to the blades is likely dominated by rain [137,138]. This would seem to imply that exclusion of consideration of hail in whirling-arm experiments may lead to inaccurate assessments of blade coating lifetimes for wind turbines deployed in regions such as the US SGP and in other regions with high hail frequency such as southern Europe, Asia, Africa and Australia (Figure 2).…”
Section: Hydroclimate and Wind Regimes At The Focus Sitesmentioning
confidence: 99%